Zasada wewnętrzności w myśli świętego Augustyna - Turzyński, Piotr (Vox Patrum, 2020)
The article presents the place of the principle of internality in the thought of Saint Augustine. The saint borrowed it from the ancient philosophical thought and turned it into the foundation of his philosophy. The principle finds its application in the rhetoric and sign theory, but also in metaphysics and the theory of knowledge. It becomes a method of discovering deeper levels of being. It is important in anthropology and here lies a way to find God, Who is deeper than the deepest in man and higher than the highest in man. The article shows the path of the Augustinian aesthetic experience thanks to which one moves from the material to the spiritual and ultimately towards fundamental beauty. The principle of interiority has its application in Christology, allowing us to find hidden glory and unchanging divinity in the suffering Christ.